Effect Of Audit Fee, Audit Tenure And Rotation Kap On Audit Quality In Indonesia Stock Exchange - Arvyanti, Hardini Oning; Budiyanto, Iwan (MALIA: Journal of Islamic Banking and Finance, 2019)
This study aimed to examine the effect of audit fees, audit tenure and rotation KAP. Groundedon literature reviews, alleged that the variable fee audit, audit tenure and KAP rotation affects the quality of auditors. The data used are the audited financial statements of companies listed on the Indonesia Stock Exchange. Testing is done by regression. Statistical test results proved that: Fee audit significant effect on audit quality, while the rotation of audit tenure and no significant effect on audit quality. The first possibility, due to the reluctance of market participants to explore further whether the auditor who issued the opinion on the audited financial statements really never experienced rotation or not. The second possibility, market participants also never pay attention to whether the financial statements audited by an auditor who has a certain reputation or not. There are various things that need to be considered for future research. Basically market players in Indonesia are mostly only consider the capital gain, so it is less likely to use fundamental analysis (financial statements) as consideration action to sell or buy shares. If the market does not consider it exhibited significantly on fundamental analysis, could also be said the market actually pay less attention to the audited results (auditor's opinion).